2011
DOI: 10.1186/1687-1499-2011-204
|View full text |Cite
|
Sign up to set email alerts
|

An SNR-based admission control scheme in WiFi-based vehicular networks

Abstract: In WiFi-based vehicular networks, the performance anomaly problem can be serious because different vehicles with diverse channel conditions access the channel by a random access protocol. In this article, we first develop a novel analytical model, which combines the vehicular traffic theory and WiFi properties to show the impact of performance anomaly at the intersection. We then propose a signal-to-noise ratio (SNR)-based admission control scheme that excludes vehicles with bad channel qualities to address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…By direct (or one-hop) broadcast approach on the control channel (CCH), analysis of the 802.11p safety-critical broadcast in VANET enviroment has been studied in [12]. To show impact of performance anomaly at the intersections in WiFi-based vehicular networks in [15], a signal-to-noise (SNR) based admission control scheme that excludes vehicles with bad channel qualities an analytical modeel has been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By direct (or one-hop) broadcast approach on the control channel (CCH), analysis of the 802.11p safety-critical broadcast in VANET enviroment has been studied in [12]. To show impact of performance anomaly at the intersections in WiFi-based vehicular networks in [15], a signal-to-noise (SNR) based admission control scheme that excludes vehicles with bad channel qualities an analytical modeel has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…al, 2013). To show impact of performance anomaly at the intersections in WiFi-based vehicular networks (Kim et. al, 2011) has developed a signal-to-noise (SNR) based admission control scheme that excludes vehicles with bad channel qualities and an analytical model.…”
Section: Introductionmentioning
confidence: 99%
“…Initialize We can easily see that the number of non-zero entries a pq on column q for all p ∈ M is at most three from Equation 8. Therefore, the number of non-zero entries on the same column in M 1 and M 2 is at most three.…”
Section: Algorithm 1: Matrix Partitioning Rule For the Constraint Matmentioning
confidence: 99%
“…Recently, Wi-Fi access technology for moving vehicles has drawn considerable attention, since it has been shown that Wi-Fi connectivity is feasible even at vehicular speed [1][2][3][4][5][6][7][8][9]. Moreover, the wide deployment of numerous WiFi access points (APs) in the urban areas [3] provides cost-effective and broadband Internet connectivity to the passengers.…”
Section: Introductionmentioning
confidence: 99%